Green Ceramic Machining: Influence of the Cutting Speed and the Binder Percentage on the Y-TZP Behavior - Anthonin Demarbaix; François Ducobu; Nicolas Preux; Fabrice Petit; Edouard Rivière-Lorphèvre (Journal of Manufacturing and Materials Processing, 2020)
The demand for inert bioceramics is always increasing in the dental field. Yttrium oxide tetragonal zirconia polycrystals (Y-TZP) are oxide ceramics which are currently used because of their interesting mechanical properties due to a toughening transformation. Industrially speaking, machining of the ceramic before sintering (green body) is very common because it allows a better productivity and it reduces crack probability during the sintering process. The goal of this paper is to determine the behavior of green ceramic during the machining operation. This study is carried out on several blanks with different binder percentages. The specific cutting energy (SCE) and the surface quality (Ra and Rz) are determined for several cutting speeds. The SCE follows a logarithmic evolution when the cutting speed increases. Despite this increase, the Ra are relatively stable whatever the cutting speed and the binder percentage. At a low cutting speed, a higher Rz value is observed caused by pullout of material. The increase of cutting speed allows to stabilize the Rz value whatever the binder percentage. This study shows that the green ceramic has a pseudo-plastic behavior whose machinability depends mainly on the interaction between the material and the cutting edge of the tool, so unlike pre-sintered ceramic or metallic part cutting speed has a low influence on the quality of the machined part.